Aqueous solubility of Cr(VI) compounds in ferrochrome bag filter dust and the implications thereof - du Preez, SP; Beukes, JP; van Dalen, WPJ; van Zyl, PG; Paktunc, D; Loock-Hattingh, MM (Water S. A., 2017)
The production of ferrochrome (FeCr) is a reducing process. However, it is impossible to completely exclude oxygen from all of the high-temperature production process steps, which may lead to unintentional formation of small amounts of Cr(VI). The majority of Cr(VI) is associated with particles found in the off-gas of the high-temperature processes, which are cleaned by means of venturi scrubbers or bag filter dust (BFD) systems. BFD contains the highest concentration of Cr(VI) of all FeCr wastes. In this study, the solubility of Cr(VI) present in BFD was determined by evaluating four different BFD samples. The results indicate that the currently applied Cr(VI) treatment strategies of the FeCr producer (with process water pH ≤ 9) only effectively extract and treat the water-soluble Cr(VI) compounds, which merely represented approximately 31% of the total Cr(VI) present in the BFD samples evaluated. Extended extraction time, within the afore-mentioned pH range, proved futile in extracting sparingly-soluble and water-insoluble Cr(VI) species, which represented approximately 34% and 35% of the total Cr(VI), respectively. Due to the deficiencies of the current treatment strategies, it is highly likely that sparingly water-soluble Cr(VI) compounds will leach from waste storage facilities (e.g. slimes dams) over time. Therefore, it is critical that improved Cr(VI) treatment strategies be formulated, which should be an important future perspective for FeCr producers and researchers alike.